2019
DOI: 10.1186/s12977-019-0470-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of herpes simplex type 1 gB, gD, and gH/gL on production of infectious HIV-1: HSV-1 gD restricts HIV-1 by exclusion of HIV-1 Env from maturing viral particles

Abstract: Background We previously showed that the gM of HSV-1 could restrict the release of infectious HIV-1 from cells. In this study, we analyzed if the four HSV-1 glycoproteins (gD, gB, and gH/gL), which are the minimum glycoproteins required for HSV-1 entry, restricted the release of infectious HIV-1. Results Of these four glycoproteins, gD and gH/gL restricted the production of infectious HIV-1 from cells transfected with an infectious molecular clone of HIV-1 (strain NL4-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…Similarly, some studies have found membrane-bound HSV-1 glycoprotein D is required for the restriction of release of infectious HIV-1 (16) and another study found several HSV-1 proteins like glycoprotein M, US3, and UL24 potently restricted the replication of HIV-1 (17).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, some studies have found membrane-bound HSV-1 glycoprotein D is required for the restriction of release of infectious HIV-1 (16) and another study found several HSV-1 proteins like glycoprotein M, US3, and UL24 potently restricted the replication of HIV-1 (17).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, some studies have found that membrane-bound HSV-1 glycoprotein D is required for inhibiting the release of infectious HIV-1 (23), and another study found that several HSV-1 proteins, such as glycoprotein M, US3, and UL24, potently restricted the replication of HIV-1 (24).…”
Section: Discussionmentioning
confidence: 91%
“…We next determined if the SARS-CoV-2 E protein would enhance or restrict the level of HIV-1Δ vpu or HIV-1 particle infectivity released from cells. HEK293 cells were co-transfected with the empty pcDNA3.1(+) vector, or pcDNA3.1(+) expressing either the SARS-CoV-2 E protein, HSV-1 gD (positive control for restriction) or gD[ΔTMCT] (a truncated form of gD that is secreted from cells and does not restrict) and pNL4-3 or pNL4-3 vpu ( 29, 30 ). As previously reported, gD potently restricted the release of infectious HIV-1 while gD[ΔTMCT] did not restrict HIV-1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The TZM-bl cell line was used as an indicator to measure HIV-1 infectivity(90)(91)(92)(93)(94)(95). Both cell lines were maintained as previously described(29,30,90). Plasmids with the entire HIV-1 NL4-3 genome (pNL4-3) and pNL4-3Δvpu were obtained from the NIH AIDS Reagent Branch.Plasmids (all pcDNA3.1(+) based) expressing E proteins (SARS-CoV-2 E: accession #QIH45055, SARS-CoV E: accession # AAP13443, MERS-CoV E: accession #ATG84849, and HCoV-OC43 E: accession #ARA15423), and the HIV-1 Vpu protein (strain NL4-3) were synthesized by Synbio Technologies with C-terminal HA-tags and were sequenced to ensure that no deletions or other mutations were introduced during the synthesis.…”
mentioning
confidence: 99%